Hotelier's guide to housekeping : learning made clean and simple - Santos, Buen (Philippines: MaxCor Publishing House, Inc, 2014)
This book will be all about the necessary skills and attitude that are needed in the housekeeping department .
Chapter1. Hotel and Resort Overview -- Chapter2. The Prerequisites -- Chapter3. Housekeeping Overview -- Chapter4. Public Area -- Chapter5. Guest Room -- Chapter6. laundry Department -- Chapter7. Executive Housekeeper -- Chapter8. Green Hotels.
Includes bibliographical references.
Keywords: HOTELIERS GUIDE; HOUSEKEEPING GUIDE; GUIDEBOOK